Perbandingan Hukum Lelang Non Eksekusi Sukarela pada E-Market Place Auction antara Indonesia dengan Amerika Serikat - Ummi Maskanah; Shintadewi Dibrata; Selly Purnama; Indri Meliani (Jurnal Syntax Admiration, 2024)
This research aims to compare non-executive voluntary auction laws on e-marketplaces between Indonesia and the United States. In Indonesia, the regulatory framework for non-executive voluntary auctions falls under the jurisdiction of the Ministry of Finance, focusing on transparency, consumer protection, and fairness in the auction process. The study highlights that despite Indonesia's adoption of digital technology to enhance auction accessibility and efficiency, regulations are still evolving to keep pace with technological advancements and market developments. Meanwhile, in the United States, non-executive voluntary auctions are detailed under federal and state laws, emphasizing consumer protection, transaction security, and robust enforcement to prevent harmful business practices. These stringent regulations encompass participant verification, bidding processes, and transaction settlement to ensure fairness and safety for all involved parties. The findings of this research indicate that differences in legal regulations, implementation, and approaches between Indonesia and the United States influence how non-executive voluntary auctions are conducted and governed in both countries. This comparison provides deep insights into the challenges and opportunities in developing legal policies that support digital economic growth in this era of globalization.